Generating web-based 3D City Models from OpenStreetMap: the current situation in Germany - Over, Martin; Schilling, Arne; Neubauer, S.; Zipf, Alexander (Computers, environment and urban systems, 2010)
This paper investigates the prospects for the generation of interactive 3D City Models based on free geo-data available from the OpenStreetMap (OSM) project and public domain height information provided by the Shuttle Radar Topography Mission. In particular, the suitability and quality of the OpenStreetMap data for 3D visualizations of traffic infrastructure, buildings and points of interest (POIs) is reviewed. The diversity and quantity of the points of interest provide new opportunities and challenges in creating customized and detailed visualization of cities. Specialized web services were implemented to filter and display the data in an acceptable manner. All applied web services of the 3D spatial data infrastructure are based on standards and draft specifications of the open geospatial consortium (OGC). The service is available online at www.osm-3d.org.